Ketosis-Prone Type 2 Diabetes: A Case Series - Sjöholm, Åke (Frontiers in Endocrinology, 2019)
Ketosis-prone type 2 diabetes ("Flatbush diabetes") carries features of both classical type 1 and type 2 diabetes and is highly prevalent in African populations. The disease, which is highly ketosis-prone, but neither chronically insulinopenic nor autoimmune, is discussed regarding pathogenesis, diagnosis and treatment from a patient case perspective.